Peasants and the art of farming : a Chayanovian manifesto - Ploeg, Jan Douwe van der (Agrarian change and peasant studies, 2014)
Peasants and the Art of Farming: A Chayanovian Manifesto focuses on the structure and dynamics of peasant farms and the historically highly variable relations that govern the processes of labour and production within peasant farms. Jan Douwe van der Ploeg argues that peasant agriculture can play an important, if not central, role in augmenting food production and creating sustainability. However, peasants today, as in the past, are materially neglected. By building on the pioneering work of Chayanov, this book seeks to address this neglect and to show how important peasants are in the ongoing struggles for food, food sustainability and food sovereignty.